2022
DOI: 10.3390/antibiotics11030369
|View full text |Cite
|
Sign up to set email alerts
|

Screening Repurposed Antiviral Small Molecules as Antimycobacterial Compounds by a Lux-Based phoP Promoter-Reporter Platform

Abstract: The emergence of multidrug-resistant strains and hyper-virulent strains of Mycobacterium tuberculosis are big therapeutic challenges for tuberculosis (TB) control. Repurposing bioactive small-molecule compounds has recently become a new therapeutic approach against TB. This study aimed to identify novel anti-TB agents from a library of small-molecule compounds via a rapid screening system. A total of 320 small-molecule compounds were used to screen for their ability to suppress the expression of a key virulenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In this framework, the inconsistency between FIB/SEM analysis and those revealed by the PI uptake assay could be explained by the prolonged exposure time used for microscopic analysis and by other factors, among those the presence of damaged DNA. Indeed, as PI intercalates with intact DNA, the lack of staining bacteria could hint at the breakage of DNA after tratment with the hit, which may be caused by the formation of ROS ( 29 , 40 42 ). Therefore, we measured the ROS formation through H2DCFDA (2′,7′-dichlorodihydrofluorescein diacetate), a nonfluorescent dye converted into the fluorescent dye DCF in the presence of intracellular ROS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this framework, the inconsistency between FIB/SEM analysis and those revealed by the PI uptake assay could be explained by the prolonged exposure time used for microscopic analysis and by other factors, among those the presence of damaged DNA. Indeed, as PI intercalates with intact DNA, the lack of staining bacteria could hint at the breakage of DNA after tratment with the hit, which may be caused by the formation of ROS ( 29 , 40 42 ). Therefore, we measured the ROS formation through H2DCFDA (2′,7′-dichlorodihydrofluorescein diacetate), a nonfluorescent dye converted into the fluorescent dye DCF in the presence of intracellular ROS.…”
Section: Resultsmentioning
confidence: 99%
“…Although not yet FDA approved, ebselen is safe in humans and is being evaluated in phase III trials for bipolar disorder, the treatment and prevention of hearing loss, Meniere’s disease, and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) ( 44 46 ). In vitro studies revealed antibacterial activity—targeting the thioredoxin reductase, thus leading to an intracellular elevation of ROS—for a wide range of infectious pathogens, including MDR Gram-positive bacteria, A. baumannii , and Mycobacterium tuberculosis complex ( 29 , 40 42 ). Our findings showed that ebselen exerts activity toward P. aeruginosa by damaging the membrane cell due to augmented membrane permeability rather than increased production of intracellular ROS.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of Ebselen as an anti-TB agent and its synergistic effect with Isoniazid have been found effective against H 37 Rv and three clinically used drug-resistant strains (JAL2287, BND320, and MYC431) . In addition, a recent study showed that Ebselen imparts low cytotoxicity against macrophages, indicating that it might be used as an anti-TB …”
Section: Repurposed Drug Candidates Against Tuberculosismentioning
confidence: 99%
“…93 In addition, a recent study showed that Ebselen imparts low cytotoxicity against macrophages, indicating that it might be used as an anti-TB. 94 4.2.2. Anticancer Drugs.…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 99%
“…While the PhoPR regulon is regulated by acidic pH, it is possible that it is directly or indirectly regulated by pH or possibly other reported signals like magnesium or chloride [6,10]. Notably, the PhoPR regulon is inhibited by treatment with ethoxzolamide (ETZ) [11][12][13], a carbonic anhydrase (CA) inhibitor [14,15], providing a potential link between carbon dioxide (CO2), pH sensing, and PhoPR regulation.…”
Section: Introductionmentioning
confidence: 99%